Increasing Economic Value in The Utilization of Goat Manure Into Organic Fertilizer in Cibeuti Village, Kawalu Tasikmalaya - Nirwanto, Yogi; Mutiarasari, Nurul Risti; Yuliyani, Leny; Salam, Rudhiana (Asian Journal of Community Services, 2024)
Goat manure is livestock waste which, if not processed properly, can cause several problems., but has economic value because it can be used as organic fertilizer. The objectives of this service are (1) to increase the capacity of livestock farmers in optimizing the use of livestock waste into organic fertilizer, (2) to reduce environmental pollution resulting from livestock waste, and (3) to increase the economic value of the results of processing this waste. This service is carried out using the training method for making organic fertilizer using Stardec technology. The results of service activities include partners being able to make organic fertilizer from animal waste using Stardec technology. Waste from livestock in the form of goat manure, feed waste and used cage bedding can be utilized properly so as to reduce environmental pollution. Apart from that, farmers and the public can use goat manure to make organic fertilizer which can be bought and sold or used for personal use. This service program received a good response from participants and the satisfaction level of training reached 80% of participants who were satisfied with this activity. The benefits of this training and in the future the production of organic fertilizer can help the economy of the surrounding community.